A Qualitative Study on E-Sports Players' Leadership Perceptions Regarding Their Team Coaches - Orçun Keçeci; Veli Onur Çelik (Pamukkale University, 2024)
Having emerged following the professionalization of digital gaming, e-sports has created its ecosystem and become a large-scale industry itself. Teams involved in this industry experience a social environment just like in other organizational structures. As e-sports is a relatively newer branch when compared to other sports branches, leadership in e-sports is not a commonly studied topic in the literature. Therefore, the aim of this study is to explore leadership perceptions of e-sports players in a comprehensive way. A team coach is often considered the leader in e-sports. The study was designed according to the principles of phenomenology, which is a qualitative research method. The semi-structured interview form developed by the researchers was used as the data collection instrument. The interviews were conducted with a group of e-sports players who met the predetermined criteria for participation in the study. The data was analyzed by using the content analysis method. First, the codes were determined, and later, the categories, and finally, the themes were identified out of these categories. Accordingly, it was found that leadership in e-sports is perceived under five themes: physical characteristics, personality traits, professional qualifications, technical skills, and management skills. Finally, it can be concluded that leadership in e-sports is quite similar to leadership in other traditional sports in many ways. However, the study showed that it has unique characteristics that need studying within the framework of the digital age and technological advancements.